Microsurgical Digits Replantation in Resource-Limited Setting: A Retrospective Study - Altam A; Obadiel Y; Alazaiza RS; Alshujaa MA; Alhajami F; Ahmed F; Al-Naggar AM; Albushtra AM; Badheeb M (Open Access Emergency Medicine, 2024)
Abdulfattah Altam,1 Yasser Obadiel,2 Rami Salim Alazaiza,1 Mohamed Ali Alshujaa,3 Faris Alhajami,1 Faisal Ahmed,4 Abdullah Mohammed Al-Naggar,5 Ahmed Mohamed Albushtra,6 Mohamed Badheeb7 1Department of General Surgery, School of Medicine, 21 September University, Sana’a, Yemen; 2Department of General Surgery, School of Medicine, Sana’a University, Sana’a, Yemen; 3Department of General Surgery, School of Medicine, Thamar University, Dhamar, Yemen; 4Department of Urology, School of Medicine, Ibb University, Ibb, Yemen; 5Department of Anesthesiology, Faculty of Medicine, Sana’a University, Sana’a, Yemen; 6Department of Orthopedics, School of Medicine, Ibb University, Ibb, Yemen; 7Department of Internal Medicine, Yale New-Haven Health/Bridgeport Hospital, Bridgeport, CT, USACorrespondence: Faisal Ahmed, Department of Urology, School of Medicine, Ibb University, Ibb, Yemen, Tel/Fax +967 4428950, Email fmaaa2006@yahoo.comBackground: This article aims to share our experiences with microsurgical finger replantation in a resource-limited setting.Methods: This multi-institutional, retrospective study included 21 cases of finger amputation that underwent microsurgical replantation, within 7 years period. Patient demographics, preoperative assessments, surgical approaches, and outcomes were documented and analyzed. A univariate analysis was performed to obtain factors associated with digit reimplantation failure.Results: Out of 21 cases included, 8 (38.1%) had complete amputations and 13 (61.9%) had incomplete amputations. Crush injuries accounted for the majority (71.4%). On average, 2.2 ± 1.1 digits were affected, with the ring finger being the most commonly injured (71.4%). The mean operative time was 121.5 ± 26.8 minutes. The success rate of digit replantation was 76.2%. During a mean follow-up of 14.3 ± 3.7 months, 85.7% of successfully replanted digits considered their replantation results satisfactory. The majority of replanted digits demonstrated active and effective holding and grasping abilities without pain or instability (76.2%). Replantation failure was associated with a higher number of affected digits (p < 0.001), longer operative time (p = 0.004), complete avulsion (p = 0.003), current smoking (p = 0.025), diabetes (p = 0.006), hypertension (p = 0.047), procedure difficulty score (p= 0.004), and occurrence of complications (p < 0.001).Conclusion: Microsurgical finger replantation can yield favorable outcomes and acceptable survival rates, even within resource-limited settings. However, this procedure requires specialized equipment and personnel that may not be available at all institutions. Influential factors in digit replantation failure, include an increased number of damaged digits, extended operative duration, complete avulsion, current smoking, diabetes, hypertension, procedure difficulty score, and postoperative complications occurrence.Keywords: microsurgery, digital replantation, amputation, resource-limited setting